Meningkatkan Hasil Belajar Siswa Melalui Pengembangan Modul Administrasi Kepegawaian Berbasis Strategi Pembelajaran Inkuiri Terbimbing - Fetri Nur Cahyani; Mohammad Arief (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2015)
The purpose of this study is: 1) to produce teaching materials in the form of Guided Inquiry-Based Learning Strategy Module for Personnel Administration for the eleventh grade students of Office Administration Program; 2) determine the feasibility of the module through the validation test; and 3) determine whether or not there is an increase in student learning outcomes between before and after using the module. This type of research is research and development. Research indicates that the product after being validated matter experts and expert modules are fit for use. Student learning outcomes after using this module increases.